Case Report: Novel CA12 Homozygous Variant Causing Isolated Hyperchloridrosis in a Chinese Child With Hyponatremia - Han, Meigui; Peng, Min; Han, Ziming; Zhu, Xiaojuan; Huang, Qian; Gu, Weiyue; Guo, Yong (Frontiers in Pediatrics, 2022)
Isolated hyperchlorhidrosis (HYCHL; OMIM 143860) is a rare autosomal recessive disorder caused by biallelic mutations in the carbonic anhydrase 12 (CA12; OMIM 603263) gene, which is characterized by abnormally high levels of salt in sweat that can lead to dehydration associated with low levels of sodium in the blood. To date, only four variants of the CA12 gene have been identified to be associated with HYCHL. Here, we presented a rare Chinese case of HYCHL in a boy with decreased food intake, mild diarrhea, severe dehydration, and hypovolemic shock. Laboratory tests showed hyponatremia and hypochloremia. He was hospitalized in our department three times. Because of recurrent attacks, WES was performed and revealed a novel homozygous missense variant c.763A>C (p.Thr255Pro) in the CA12 gene (NM_001218.5). 0.9% sodium chloride (NaCl) solution was orally administered until 1 year and 6 months of age. Followed up to 3 years of age, the patient showed good growth and development without similar manifestations. This study reported a novel CA12 gene mutation leading to HYCHL for the first time in China, which enriched the genotype of HYCHL and emphasized the early suspicion and identification of the rare condition to adequate treatment.